Comparison of volatile aroma constituents of Salacca zalacca (Gaertn.) Voss extracted by conventional and non-conventional extraction methods - Nur Nadhirah binti Hilmi
Salacca zalacca (Gaertn.) Voss is a species of palm tree native to Southwest Java and North Sumatra in Indonesia. It is one of the exotic fruits in Malaysia and is locally known as salak. It has a reddish-brown scaly skin with pleasant pineapple, pear and banana-like aromas. Several studies have been conducted on the volatile aroma constituents of S. zalacca, however, no such study was done on S. zalacca species cultivated in Malaysia. Furthermore, the limitations of the conventional extraction methods have emphasized the need for a faster and environmentally friendly extraction method. The aims of the research were to extract the volatile aroma constituents of S. zalacca using steam distillation, solvent extraction and supercritical fluid extraction (SFE) methods, to identify the possible volatile aroma constituents present in the extracts by GC/MS analysis and to compare the volatile aroma constituents extracted by these methods. The solvents used in the solvent extraction method were hexane, diethyl ether and dichloromethane (DCM), whereas carbon dioxide was the supercritical fluid used in the SFE. Comparison of percentage yields found that diethyl ether solvent extraction had the highest percentage yield (0.5692 %) followed by SFE (0.2516 %), steam distillation (0.1855 %), DCM solvent extraction (0.1358 %) and hexane solvent extraction (0.0511 %). SFE was found to be the most efficient extraction method as it produced satisfactory amount of yield at the shortest extraction period with the least amount of sample. It also did not produce any solvent waste. The GC/MS analysis found that steam distillation was not a suitable extraction method since it produced impure extract. Diethyl ether solvent extraction produced the highest total number of volatile aroma constituents with a total of 38 possible compounds followed by hexane (21 compounds) and DCM (19 compounds). Seven of the possible compounds in the diethyl ether solvent extract have pharmaceutical/nutraceutical benefits. Three of these compounds were (E)-15-heptadec15-enal (4.46 %), palmitic acid (3.82 %) and γ-sitosterol (3.41 %). On the other hand, SFE method at optimal condition (40 MPa/70 ºC) had extracted a total of 29 possible compounds with seven of them identified to have pharmaceutical/nutraceutical benefits. Examples of these compounds were γ-sitosterol (31.8 %), dihydrobrassicasterol (3.27 %) and stigmasterol (1.81 %). Comparison of volatile aroma constituents between the diethyl ether solvent extraction and the SFE method found that diethyl ether solvent extraction had extracted higher number and concentration of low molecular weight compounds while the SFE method had extracted higher number and concentration of high molecular weight compounds. Concentration of γ-sitosterol was found to be significantly high in the SFE extract. In conclusion, SFE is a green extraction method which is capable of efficiently and selectively extract targeted compounds especially those with high molecular weight.